Navigating Social Work Field Placements: Barriers and Adaptive Strategies Among Students with Disabilities in Higher Education - Kisy Anif Ngestiti (UIN Sunan Kalijaga Yogyakarta, 2025)
Inclusive higher education has become a central agenda in advancing social justice; however, its implementation in professional education-particularly in social work field placements-remains inconsistent. This study examines the barriers faced by students with disabilities undertaking Social Work Field Placement (Praktikum Pekerjaan Sosial, PPS) within the Social Welfare Program at UIN Sunan Kalijaga, Indonesia, as well as the adaptive strategies they employ. Using a qualitative case study design, data were collected through in-depth interviews, observations, and document analysis involving three students with disabilities and two field supervisors. Thematic analysis reveals that students encounter multiple barriers, including limited mobility, insufficient institutional support from placement agencies, social stigma, and psychosocial stressors. The findings further identify four predominant coping strategies: seeking social support, self-regulation, acceptance and adjustment, and task simplification facilitated through supervisory mediation. Drawing on the Social Model of Disability, this study demonstrates that students’ challenges are primarily produced by non-inclusive field environments rather than individual impairments. Coping Strategy Theory is employed to explain the diversity of students’ adaptive responses to field-based stress and uncertainty. The study highlights that successful field placements for students with disabilities depend on systemic support, responsive supervision, and inclusive field placement design. These findings contribute to international debates on inclusive professional education and offer practical insights for developing disability-responsive field education policies within social work programs, particularly in Global South contexts. Keywords: students with disabilities, social work field placement, adaptive strategies, social model of disability, coping theory Pendidikan tinggi inklusif merupakan agenda penting dalam mendorong keadilan sosial, namun implementasinya dalam pendidikan profesional, khususnya praktikum pekerjaan sosial masih menghadapi berbagai tantangan. Penelitian ini bertujuan mengkaji hambatan serta strategi adaptasi mahasiswa disabilitas dalam menjalani Praktikum Pekerjaan Sosial (PPS) di Program Studi Ilmu Kesejahteraan Sosial UIN Sunan Kalijaga. Menggunakan pendekatan kualitatif dengan desain studi kasus, data dikumpulkan melalui wawancara mendalam, observasi, dan telaah dokumen terhadap tiga mahasiswa disabilitas dan dua supervisor praktikum. Hasil Analisis menunjukkan bahwa mahasiswa disabilitas menghadapi hambatan berlapis yang bersifat struktural, sosial, dan psikososial, meliputi keterbatasan mobilitas, lemahnya dukungan lembaga mitra, stigma sosial, serta tekanan mental personal. Temuan juga mengidentifikasi empat strategi adaptasi utama, yaitu pencarian dukungan sosial, pengaturan diri, penerimaan dan penyesuaian, serta penyederhanaan tugas yang dimediasi oleh supervisor. Dengan menggunakan Social Model of Disability, penelitian ini menunjukkan bahwa kesulitan mahasiswa lebih banyak diproduksi oleh lingkungan praktik yang belum inklusif daripada oleh disabilitas itu sendiri. Sementara itu, Coping Strategy Theory membantu menjelaskan variasi respons adaptif mahasiswa dalam menghadapi tekanan praktik. Studi ini menegaskan bahwa keberhasilan PPS mahasiswa disabilitas sangat ditentukan oleh dukungan sistemik, supervisi yang responsif, dan desain praktik lapangan yang inklusif. Temuan ini berkontribusi pada pengembangan kebijakan dan pedoman PPS berbasis keadilan sosial di pendidikan pekerjaan sosial. Kata Kunci: mahasiswa disabilitas, praktik pekerjaan sosial, strategi adaptasi, social model of disability, coping theory